Indoor Air Quality Assessment in an Aging Educational Building: A Case Study of the ICRC Office, UTHM - CHE BAHARUM BIN CHE BUSU, CHE MUHAMMAD NAQEB BIN CHE BAHARUM; Prof. Madya Ts. Dr. Azian Hariri (Research Progress in Mechanical and Manufacturing Engineering, 2026)
Indoor air quality (IAQ) plays an important role in maintaining occupant health, comfort, and productivity, particularly in office environments. Aging buildings are often associated with ventilation limitations and deteriorated systems that may contribute to indoor pollutant accumulation. This study presents an IAQ assessment conducted at the Industry Community and Relations Centre (ICRC) Office, Universiti Tun Hussein Onn Malaysia (UTHM), an educational building established in 1999. The assessment involved walkthrough inspection, physical measurements using sensor-based instruments, subjective evaluation through an occupant questionnaire survey, and comparison with the Industry Code of Practice on Indoor Air Quality (ICOP IAQ 2010) guidelines and previous IAQ data. The subjective assessment focused on occupants’ perceptions of indoor comfort and the occurrence of IAQ-related symptoms during working hours. Key physical parameters evaluated include air temperature, relative humidity, and air movement, while chemical parameters include carbon dioxide, carbon monoxide, ozone, formaldehyde, particulate matter, and total volatile organic compounds. Most parameters were within acceptable limits; however, particulate matter (PM₁₀) exceeded the ICOP IAQ 2010 limit of 0.15 mg/m³, with concentrations of 0.328 mg/m³ on Day 1 and 0.220 mg/m³ on Day 2. Elevated PM₁₀ levels are likely influenced by infrequent housekeeping activities and carpeted flooring. Correlation analysis indicated an association between increased particulate matter levels and reported symptoms such as fatigue and headaches, suggesting potential Sick Building Syndrome (SBS) conditions. The findings highlight the importance of continuous IAQ monitoring and proper maintenance of ventilation systems in aging educational buildings.